2006
DOI: 10.1055/s-2006-941484
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine Treatment of Major Depressive Episodes in the Course of Psychotic Disorders

Abstract: During the course of psychotic disorders, patients often suffer from intercurrent major depressive episodes (MDEs), and suicides frequently occur. This constellation challenges further improvements in psychopharmacological therapy. The antidepressant duloxetine was recently introduced as a novel reuptake inhibitor of serotonin and noradrenaline. We provide the first reports on duloxetine treatment of MDEs in the course of psychotic disorders. In two cases this substance was successfully involved as an add-on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Accordingly, treatment guidelines recommend treatment of depressive episodes during the course of schizophrenia with antidepressants [3]. Based on these reports, clinicians may consider the use of selective serotonin and norepinephrine reuptake inhibitors such as duloxetine in the treatment of schizophrenic patients suffering a depressive episode [10].…”
Section: Referencesmentioning
confidence: 99%
“…Accordingly, treatment guidelines recommend treatment of depressive episodes during the course of schizophrenia with antidepressants [3]. Based on these reports, clinicians may consider the use of selective serotonin and norepinephrine reuptake inhibitors such as duloxetine in the treatment of schizophrenic patients suffering a depressive episode [10].…”
Section: Referencesmentioning
confidence: 99%
“…As far as depression itself is concerned the data are much more limited since only a very low percentage of clinical studies are using an adequate rating scale such as the Calgary Depression Scale (CDS). Positive data have been published for sertraline in post psychotic depression (Kirly, 1998) and for duloxetine on case reports (Zink, 2006). The situation is worse for comorbid anxiety where the interaction of specifi c anxiety subtypes and psychosis has been quite insuffi ciently studied (Huppert, 2005).…”
Section: So 1003 Update On Treatment Of Depression and Anxiety In Scmentioning
confidence: 99%
“…Moreover, duloxetine has an analgetic potency which also could be demonstrated in randomised controlled trials [1,16,23] . Zink et al reported on successful duloxetine treatment of major depressive episodes in the course of psychotic disorders [32] . Therefore duloxetine is especially useful in depressive episodes with somatic symptoms [8,13] .…”
Section: Introductionmentioning
confidence: 99%